Effects of Compost and Organic Amendments on Weed Control - Kanissery, Ramdas; Bashyal, Mahesh (EDIS, 2023)
Using compost and soil amendments is beneficial to Florida citrus groves. Given the sandy nature of Florida soils and their low organic matter and cation exchange capacity (CEC), adding compost and organic amendments (e.g., humic acid) can enhance the ability of soil to retain water and nutrients. These practices can also boost soil microbial activity and improve soil health. Previous research has shown that yield losses from huanglongbing (HLB) affected trees correlate with low fibrous root densities and reduced root system capacity for water and nutrient uptake. Compost and organic amendments can thus aid citrus growers by improving overall soil physical, chemical, and biological properties. However, any strategies to boost tree growth can also potentially boost weed growth. So it is essential to understand the impacts of these soil management practices on weed emergence and infestation in citrus groves.